Development of a Case Method-Based Interactive E-Module on Acid–Base Materials for Grade XI Senior High School Students - Sepsusilawati; Jasrial (JPI: Jurnal Pustaka Indonesia, 2026)
Students' limited conceptual understanding of acid-base material remains a challenge in chemistry learning due to the material's abstract and complex nature. On the other hand, the demands of 21st-century education require students to develop critical thinking, problem-solving, and independent learning skills. This study aims to develop an interactive e-module based on the case method on acid and base material and test its validity, practicality, and effectiveness. The study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were obtained through expert validation sheets, practicality questionnaires, and learning outcome tests, which were analyzed descriptively and quantitatively. The results showed that the developed e-module met the criteria for being very suitable for learning. The practicality test by students yielded a percentage range of 90.85% to 94.14%, with the attractiveness aspect achieving the highest score of 94.14%. From an effectiveness perspective, there was a significant increase in learning outcomes, as indicated by a rise in students' average score from 42.33 in the pretest to 89.17 in the posttest during the small-group stage. Furthermore, the average posttest score during the implementation phase was 81.34, with a classical completion rate of 85.71%. These findings demonstrate that integrating the case method with interactive multimedia can help students connect the concepts of acids and bases to contextual problems, thereby enhancing conceptual understanding and engagement. Therefore, the interactive e-module based on the case method has the potential to be an effective digital teaching material innovation to support chemistry learning that is more contextual, meaningful, and oriented towards developing 21st-century competencies.